VoLTE call setup delay optimization based on signaling message - Bao GUO; Yang ZHANG (Dianxin kexue)
VoLTE wireless spectrum utilization efficiency is better than that of the traditional CS voice.The introduction of high-definition voice and video codes significantly improves the communication quality.VoLTE call setup duration has been significantly shortened compared to the traditional CS voice.Analyzing the factors in causing call setup delay of VoLTE was focused,and corresponding solutions about the VoLTE call setup delay optimization was put forward based on the signaling message in different stages,including paging,domain selection,resource reservation.